Bis{N′-[3-(4-nitrophenyl)-1-phenylprop-2-en-1-ylidene]-N-phenylcarbamimidothioato}zinc(II): crystal structure, Hirshfeld surface analysis and computational study - Tan, Ming Yueh; Kwong, Huey Chong; Crouse, Karen A.; Ravoof, Thahira B. S.; Tiekink, Edward R. T. * (International Union of Crystallography, 2021)
The title zinc bis(thiosemicarbazone) complex, [Zn(C22H17N4O2S)2], comprises two N,S-donor anions, leading to a distorted tetrahedral N2S2 donor set. The resultant five-membered chelate rings are nearly planar and form a dihedral angle of 73.28 (3)°. The configurations about the endocyclic- and exocyclic-imine bonds are Z and E, respectively, and that about the ethylene bond is E. The major differences in the conformations of the ligands are seen in the dihedral angles between the chelate ring and nitrobenzene rings [40.48 (6) cf. 13.18 (4)°] and the N-bound phenyl and nitrobenzene ring [43.23 (8) and 22.64 (4)°]. In the crystal, a linear supramolecular chain along the b-axis direction features amine-N—H...O(nitro) hydrogen bonding. The chains assemble along the 21-screw axis through a combination of phenyl-C—H...O(nitro) and π(chelate ring)–π(phenyl) contacts. The double chains are linked into a three-dimensional architecture through phenyl-C—H...O(nitro) and nitro-O...π(phenyl) interactions.